The Care Dependency Levels of the Inpatients in The Palliative Care Center and Influencing Factors - Pekince, Hatice; Aslan, Hakime (Bolu Abant İzzet Baysal Üniversitesi, 2021)
Purpose: This study has been conducted as a descriptive-cross sectional study with the purpose of examining care dependency levels of inpatients in palliative care center and factors affecting. Methods: The universe of the research consists of inpatients in a city hospital palliative care clinic in eastern Turkey. The sample size was determined to be 102 patients by conducting power analysis. A random sampling method was used. The study has been conducted between January 2019-February 2020. The data of the research were collected by using the questionnaire form containing socio-demographic information and the “Care Dependency Scale (CDS)”. SPSS 21.0 package program was used for statistical evaluation, and percentage, mean, standard deviation, Mann Whitney U and Kruskal-Wallis H tests were used in the analysis of data. Results: It was determined that mean score of the care dependency scale (CDS) was 40.1±6.0. It was determined that there was negative relationship between age and care dependence scale (r=-.432**, p=.000). The difference between gender, marital status, education level, diagnosis time and getting help during care variables and CDS score average was found to be statistically significant. (p<0.05). Patients were most dependent on these activities; hygiene, dressing and undressing and mobility, respectively. Conclusions: Patients in palliative care center were found to have high levels of care dependency.

Amaç: Bu araştırma, palyatif bakım merkezinde yatan hastaların bakım bağımlılık düzeylerini ve bunu etkileyen faktörlerin incelenmesi amacıyla tanımlayıcı olarak yapılmıştır. Yöntem: Araştırmanın evrenini Türkiye’nin doğusunda yer alan bir şehir hastanesinin palyatif bakım kliniğinde yatan hastalar oluşturmaktadır. Örneklemini, power analizi yapılarak belirlenen 102 hasta oluşturmuştur. Örneklemin evrenden seçilmesinde, rastgele örnekleme yöntemi kullanılmıştır. Çalışma Ocak 2019-Şubat 2020 tarihleri arasında yürütülmüştür. Araştırmanın verileri sosyo-demografik bilgileri içeren form ve “Bakım Bağımlılık Ölçeği” kullanılarak toplanmıştır. İstatistiksel değerlendirmede SPSS 21.0 paket programı, verilerin analizinde yüzde, ortalama, standart sapma, Mann Whitney U ve Kruskal-Wallis H testleri kullanılmıştır. Bulgular: Araştırmaya katılan hastaların bakım bağımlılığı ölçeği (CDS) puan ortalamasının 40.1±6.0 olduğu saptanmıştır. Yaş ile bakım bağımlılığı ölçeği arasında negatif yönde çok güçlü ilişki olduğu saptanmıştır (r=-.402**, p=.000). Cinsiyet, medeni durum, eğitim seviyesi, tanı süresi ve bakımda yardım alma değişkenleri ile bakım bağımlılığı arasındaki farkın istatistiksel olarak anlamlı olduğu saptanmıştır (p<0.05). Hastaların en çok hijyen, giyinme-soyunma ve hareketlilik aktivitelerinde bağımlı oldukları saptanmıştır. Sonuç: Bu sonuçlar doğrultusunda; palyatif bakım merkezinde yatan hastaların bağımlılık düzeylerinin yüksek olduğu belirlenmiştir.
Palyatif Bakım Merkezinde Yatan Hastaların Bakım Bağımlılık Düzeyleri ve Etkileyen Faktörler
Keywords: Clinical Sciences; Klinik Tıp Bilimleri